Improving rowing performance by adjusting oar blade size and angle - Tran, M. T. K.; Yang, M. D.; van Nieuwburg, W.; van Spreuwel, B. (TU Delft, 2022)
A 1:5 scaled rowing boat had been designed by a previous research group to determine the performance of rowing blades with different sizes and blade angles. In this research modifications were done to allow more control of the rowing motion. The aim of this study is to assess whether an angled oar blade can reach faster speeds with the same input power. This is done by collecting data with force and position sensors. With the collected data, the input power and speed of the rowing boat can be compared between several modified oar blades. The results of the tests in the towing tank show that it is very likely that the rowing boat can go faster with the same input power by adjusting the oar blade angle.